Anthropometric indicators may explain the high incidence of follicular lymphoma in Europeans: Results from a bidirectional two-sample two-step Mendelian randomisation - Zhou, Yanqun; Zhang, Xiongfeng; Li, Xiaozhen; Zhu, Guoqing; Gao, Tianqi; Deng, Yingying; Huang, Liming; Liu, Zenghui (Gene, 2024)
••The incidence of follicular lymphoma is significantly higher in European populations compared to non-European populations.••We do not know whether these differences are caused by metabolic phenotypes linked to anthropometric indicators.••Given the reliability of Mendelian randomization, our study aims to employ this methodology to investigate genetic associations and potential mediators between anthropometric indicators and Non-Hodgkin's lymphoma.••Our findings indicate a causal association between higher fat-free mass and standing height in Europeans and an elevated risk of follicular lymphoma. These associations are mediated by elevated basal metabolic rates, which could potentially contribute to the higher incidence of follicular lymphoma observed in this population. Non-Hodgkin's lymphoma incidence rates vary between European and Asian populations. The reasons remain unclear. This two-sample two-step Mendelian randomisation (MR) study aimed to investigate the causal relationship between anthropometric indicators (AIs) and diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) and the possible mediating role of basal metabolic rate (BMR) in Europe. We used the following AIs as exposures: body mass index (BMI), whole-body fat mass (WBFM), whole-body fat-free mass (WBFFM), waist circumference(WC), hip circumference(HC), standing height (SH), and weight(Wt). DLBCL and FL represented the outcomes, and BMR was a mediator. A two-sample MR analysis was performed to examine the association between AIs and DLBCL and FL onset. We performed reverse-MR analysis to determine whether DLBCL and FL interfered with the AIs. A two-step MR analysis was performed to determine whether BMR mediated the causality. WBFFM and SH had causal relationships with FL. A causal association between AIs and DLBCL was not observed. Reverse-MR analysis indicated the causal relationships were not bidirectional. Two-step MR suggested BMR may mediate the causal effect of WBFFM and SH on FL. We observed a causal relationship between WBFFM and SH and the onset of FL in Europeans, Which may explain the high incidence of follicular lymphoma in Europeans.